Nonlinear finite element aeroelastic modelling of reinforced skin panels in supersonic flows - Pacheco, Douglas Ramalho Queiroz (2018)
Panel flutter is an aeroelastic phenomenon that can cause critical structural failure in aerospace vehicles operating at supersonic speeds. A reliable modelling of such phenomenon is crucial for safely predicting the lifespan of aircraft skin, thus being of great importance to aerospace structural design. The vast majority of works published on this subject treat each skin panel as an isolated structure. In reality, however, aircraft skin is typically composed of large panels mounted over spars, stringers and other types of reinforcement elements. The presence of such stiffening components ends up subdividing the panel into multiple smaller cells that can interact during flutter, thereby making the aeroelastic motion potentially more complex and dangerous. Moreover, stiffeners are also deformable structures, which therefore take part in the dynamics of the problem. In this context, the present work deals with the study and implementation of a computational finite element model for the analysis of nonlinear flutter in stiffened panels. A combination of the Mindlin plate model and the Timoshenko beam model, both with geometric non-linearities, is employed. The model and the analyses tackle both isotropic and laminated panels. The aerodynamic forces are computed through first-order piston theory, which provides good results for high-supersonic flows. The energy equations are discretised via the Finite Element Method, and the resulting aeroelastic equations of motion are solved in the time domain through an iterative Newmark-type integration scheme. The final code is verified and validated through comparison with numerical solutions from the literature. As far as results and analyses are concerned, the present work focuses on three main aspects, thereby aiming to fill an existing gap in panel flutter literature: a) lnvestigating how stiffeners behave during flutter, from a dynamic perspective, and how their vibration affects the overall aeroelastic motion; b) Studying the infiuence of stiffener geometry on such effects; and c) Assessing the inaccuracies of the single-panel model by systematically comparing its results with those from the present multi-cell model. Results reveal novel aeroelastic phenomena arising from the modelling of stiffeners as flexible structural elements. Furthermore, the popular assumption of ideal fixation is proven to be potentially unconservative regarding the onset of flutter and the intensity of vibrations